2017
DOI: 10.3390/nu9040350
|View full text |Cite
|
Sign up to set email alerts
|

Sport Nutrition Knowledge, Behaviors and Beliefs of High School Soccer Players

Abstract: For adolescent athletes (14–18 years), data on sport nutrition knowledge, behaviors and beliefs are limited, especially based on sex, race/ethnicity and socioeconomic status. High school soccer players (n = 535; 55% female; 51% White, 41% Latino; 41% National School Lunch Program (NSLP) participants (80% Latino)) completed two questionnaires (demographic/health history and sport nutrition). The sport nutrition knowledge score was 45.6% with higher scores in NSLP-Whites vs. NSLP-Latinos (p < 0.01). Supplement k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 46 publications
3
64
1
3
Order By: Relevance
“…In another study of young Kenyan female athletes, middle-distance and long-distance runners were found to exhibit one or more subclinical and/or clinical components of the RED-S, including a greater risk for LEA and menstrual dysfunction than controls 52. A study of sport nutrition knowledge, behaviours and beliefs across sex, race/ethnicity and socioeconomic status in high school soccer players identified that general sports nutrition knowledge is lower in adolescent soccer players compared with prior reports in adolescent athletes and that specifically females and Latinos may benefit from sport nutrition education 53. Published research is greatly lacking on RED-S in African-American, Hispanic and Asian athletes, with a few exceptions 54 55.…”
Section: Introductionmentioning
confidence: 86%
“…In another study of young Kenyan female athletes, middle-distance and long-distance runners were found to exhibit one or more subclinical and/or clinical components of the RED-S, including a greater risk for LEA and menstrual dysfunction than controls 52. A study of sport nutrition knowledge, behaviours and beliefs across sex, race/ethnicity and socioeconomic status in high school soccer players identified that general sports nutrition knowledge is lower in adolescent soccer players compared with prior reports in adolescent athletes and that specifically females and Latinos may benefit from sport nutrition education 53. Published research is greatly lacking on RED-S in African-American, Hispanic and Asian athletes, with a few exceptions 54 55.…”
Section: Introductionmentioning
confidence: 86%
“…In these previous studies, boiled lentils were compared to high-GI foods (i.e., mashed potatoes with egg whites added to match for protein), but these meals may not be typical before matches for soccer players (or other athletes involved in sports with high-intensity intervals). Endurance athletes often consume sport nutrition bars [23] and surveys of youth soccer players indicate that about 37% consume food, such as sport nutrition bars, up to 1 h before games in an attempt to improve performance [24]; however, the effectiveness of a sport nutrition bar for soccer performance has never been evaluated. From a practical point of view, using sport nutrition bars (high-CHO) can be considered when time is limited before the start of competition.…”
Section: Introductionmentioning
confidence: 99%
“…What if nutrition education were introduced at an earlier age and performance enhancing dietary habits began before the athletes started competing at the collegiate level? Until now, multiple studies have acknowledged the lack of nutrition knowledge in adolescents [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ], but few studies have taken the next step in determining how to best educate adolescents on nutrition-related topics.…”
Section: Introductionmentioning
confidence: 99%
“…Many adolescent athletes believe that diet is important for sport performance while also reporting their diet does not currently meet recommended nutritional requirements for sport [ 5 , 8 ]. When incoming collegiate freshman football players were asked about their desire to learn about nutrition related topics, 97% of athletes expressed a desire to learn about nutrition for peak performance, 81% sought to learn about weight gain, and 71% wanted tips on eating out [ 10 ].…”
Section: Introductionmentioning
confidence: 99%